DAKWAH DAN JIHAD DALAM ISLAM: STUDI ATAS PEMIKIRAN K.H.M. HASYIM ASY’ARI - Muh Shofi Al Mubarok; Sudarno Shobron (Profetika: Jurnal Studi Islam, 2015)
Muhammad Hasyim Asy’ari was a scholar known as scholars and Indonesian freedom fighters. The formulation of the problem in this paper begin with a question; how the propaganda struggle and Jihad Muhammad Hasyim Asy’ari and how the activity and its contribution in propaganda and jihad. the goal is to understand his thoughts in propaganda and jihad, so it can be a model for the next generation and society in general. Methods This study uses primary data source that examines the writings of Muhammad Hasyim Asy’ari, and the secondary source data. These two sources are obtained using literature study (library research). Therefore, this research includes bibliographic and qualitative research types, purely library research (library research) with historical-philosophical approach. The data obtained will be analyzed sequentially and interactionist which consists of three stages: 1) Reduction of data, 2) Presentation of data, 3) Withdrawal conclusion or verification.Keywords: propaganda; jihad; muhammad hasyim asy’ari.